First identification and whole genome characterization of rotavirus C in pigs in Zambia - Harima, Hayato; Qiu, Yongjin; Sasaki, Michihito; Ndebe, Joseph; Penjaninge, Kapila; Simulundu, Edgar; Kajihara, Masahiro; Ohnuma, Aiko; Matsuno, Keita; Nao, Naganori; Orba, Yasuko; Takada, Ayato; et al. (Virology (New York, N.Y.), 2025)
Rotavirus C (RVC) causes acute gastroenteritis in neonatal piglets. Despite the clinical importance of RVC infection, the distribution and prevalence in pig populations in most African countries remains unknown. In this study, we identified RVC in Zambian pigs by metagenomic analysis. The full genome sequence of the RVC revealed two different VP4 sequences, implying that two different RVC strains (ZP18-77-c1 and ZP18-77-c2) were present in the same sample. Genetic analyses demonstrated that all segments of ZP18-77-c1 and ZP18-77-c2 showed high nucleotide sequence identities (87.7–94.5%) to known porcine RVC strains, and ZP18-77-c1 and ZP18-77-c2 strains were assigned to genotype constellations, G1-P[4]/P[14]-I13-R5-C5-M1-A7-N9-T10-E5-H1. We further screened RVC genomes among pig feces collected in Zambia (n = 147) by RT-qPCR, and 78 samples (53.1%) were positive. This study demonstrated the first full genome sequence of African RVC strains with a relatively high prevalence of RVC infection in the pig populations in Zambia. •First detection of rotavirus C (RVC) in Zambia.•RVC was associated with diarrhea in weaning/fattening pigs in Zambia.•High prevalence of RVC infection in Zambian pigs.